Being modern : the cultural impact of science in the early twentieth century - Bud, Robert; Greenhalgh, Paul; James, Frank; Shiach, Morag (UCL Press, 2018)
In the early decades of the twentieth century, engagement with science was commonly used as an emblem of modernity. This phenomenon is now attracting increasing attention in different historical specialties. Being Modern explores engagement with science across culture from the end of the nineteenth century to approximately 1940.